Switching Converter with Highly Stable Delta-Sigma Modulator - K., Diwakar; C. Senthil, Pari; Ajay Kumar, Singh (2008)
The switching converter with the existing second order, single stage, single bit, unity gain, discrete Delta-Sigma modulator (DSM) cannot be used for full range (-1 to +1) of input signals. The DSM becomes unstable when the input signal is above +/- 0.7. The output of the second integrator saturates the operational amplifier which is used as comparator in the quantizer and hence, the switching converter (SC) becomes unstable. In the present paper, a novel DSM based SC is proposed which can operate for the wider range of input signal without causing unstable situation. The upper bounds on the integrator outputs are directly proportional to the dc input signal and never increase abruptly. The range of converter output voltage is increased by about 30%.